The geopolitical situation of Ukraine after the „Orange Revolution” - Budka, Krzysztof; Tychoniec, Alicja Ewa (Journal of Education, Health and Sport, 2017)
The article presents the conditions for the Orange Revolution in Ukraine. The primary determinants of social protest in Ukraine, pursuant to which the elections were repeated, have been identified. The geopolitical changes, including the state reforms announced by the opposition candidate, V. Yushchenko, have been characterized.